ANALYSIS OF FACTORS THAT INFLUENCE THE PERFORMANCE OF PLN IN IMPROVING COMMUNITY SERVICES IN THE DISTRICT OF MEDAN TIMUR - Tanoto, Nico Samah (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2022)
The purpose for this research is to analyze factors that influence the performance of PLN in improving community services in the district of Medan Timur. The Research Method is quantitative method with Survey method which use questionnaire as research instrument to collects data. The Population in this research is every consumen of PLN Medan Timur estimate at 71.383 Consumen Number. Using Slovin formula, n = N / (1 + (N x e²)) with Margin of Error 10% so that obtained 100 Respondent for Independent and multiple linear regression test that will be used as a tools to learn how much influence does Independent Variable cause to Dependent variable. Research results shows that Creativity and Innovation Factors gives significant effects from partial even simultant in improving community sevices in the District of Medan Timur. Creativity and Innovatin Variable shows Improvement of Community Services By 26%.